PENGARUH RETURN ON ASSET (ROA), CURRENT RATIO (CR), DEBT TO ASSET RATIO (DAR), DAN CAPITAL INTENSITY RATIO (CIR) TERHADAP AGRESIVITAS PAJAK - R. Neneng Rina Andriani; Adil Ridlo Fadillah (JURNAL AKUNTANSI, 2019)
The purpose of Tthis research is to know and analyze the influence of Return on Assets (ROA), Current Ratio (CR), Debt to Assets Ratio (DAR), and Capital Intensity Ratio (CIR) to Tax Aggressiveness. The population in this study is the Manufacturing Compinies listed in Indonesia Stock Exchange for the period 2012-2017. Sampling method is purposive sampling with some of criteria that procedure a final sample in quantities of nineteen (19) companies as the sampel. The research method used is secondary data. Technique of data analysis that be used is analysis regresion of pooled data Ordinary Least Square (OLS) method used software SPSS version 16.0. The result show that simultaneouslyRReturn on Assets (ROA), CCurrent Ratio (CR), Debt to Asset Ratio (DAR), and Capital Intensity Ratio (CIR) have significant effect based toTTax Aggressiveness. Partially,RReturn on Assets (ROA) has positive and significant effect toTTax Aggressiveness. Debt to Asset Ratio has negative and significant effect to Tax Aggressiveness. While Current Ratio (CR) and Capital Intensity Ratio (CIR) have no effect to Tax Aggressiveness.